2024
DOI: 10.1101/2024.02.14.580411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictable functional biogeography of marine microbial heterotrophs

Emily J. Zakem,
Jesse McNichol,
J.L. Weissman
et al.

Abstract: Microbial heterotrophs (`picoheterotrophs') drive global carbon cycling, but how to quantitatively organize their functional complexity remains unclear. Here, we generate a global-scale, mechanistic understanding of marine picoheterotrophic functional biogeography with a novel model-data synthesis. We build picoheterotrophic diversity into a trait-based marine ecosystem model along two axes: substrate lability and optimization for growth rate (copiotrophy) vs. substrate affinity (oligotrophy). Using genetic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Overall, these intermediate growth clusters appeared to be more flexible metabolically and faster-growing than the slow-growing specialist clusters but more specialized and slower growing than the fast-growing generalist cluster. The intermediate growth clusters corroborate a recent modeling study which suggested that the dominant heterotrophic group in the subsurface ocean might be slow-growing copiotrophs 2 .…”
Section: Emergent Metabolic Clusterssupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, these intermediate growth clusters appeared to be more flexible metabolically and faster-growing than the slow-growing specialist clusters but more specialized and slower growing than the fast-growing generalist cluster. The intermediate growth clusters corroborate a recent modeling study which suggested that the dominant heterotrophic group in the subsurface ocean might be slow-growing copiotrophs 2 .…”
Section: Emergent Metabolic Clusterssupporting
confidence: 88%
“…Classification of heterotrophic microbes into metabolic functional guilds can provide a framework for coalescing diverse microbial communities 1 into more tractable units for incorporation into biogeochemical models 2 . Historically, we have grouped marine microbial heterotrophs into copiotrophic organisms, which thrive in high resource environments and generally have faster growth rates with flexible metabolisms, and oligotrophic organisms, which dominate resource poor environments and have slower growth rates 3 .…”
mentioning
confidence: 99%